IKONOGRAFI RELIEF CANDI PENATARAN - Afrizal, A. (Acintya, 2017)
The article titled â€œKajian Ikonografi Relief Candi Penataranâ€ was intended to find the textual andcontextual meaning of relief that was located in the Penataran Temple cluster, especially PendapaTeras II Penataran Temple. With iconography approach would be obtained a deeper and broadermeaning of an art work, although understanding on the contextual and symbolic aspects was alsoneeded. Thus, in the study of iconography there were aspects of diachronic, synchronic, and symbolic. In the study of Sri Tanjung relief, its diachronic aspects related to the history of temple relief asa dialectical motion, idea, or artistic concept based on the progress from beginning to end based onthe time sequence. The synchronic aspect related to the interrelatedness of the various social, cultural, and even mental facts of the society of an age in which art was produced. In the case, the SriTanjung relief would find its context when examined through the search of socio-cultural history atthe time of temple relief making and been analyzed based on the idea of relief presenting. In the studyof Sri Tanjung relief, it was understood that humans who had been willing to think about their Lord,humans who had been willing to obey or being obedient as an expression of their love for the God,and humans who had devotion to their God. If humans had reached a pure level in their heart andmind then that was where humans reached perfection. Perfection in the concept of Java meant humans had merge or â€˜manunggalâ€™ with God. Manunggal meant God was inside humans, in their heart thatcould not be separated. Perfection in terms of its form was because they was a perfect manifestationor image of Godâ€™s image, he reflected Godâ€™s name and attribuuted in complete. The perfection in termsof knowledge was because they had attained the highest level of consciousness, that was, to realizethe unity of their essence with God.Keywords: adaptation, iconography, morality, Sri Tanjung relief